ANALISIS BIAYA DAN WAKTU PADA PEMBANGUNAN RUMAH SAKIT TINGKAT III BRAWIJAYA SURABAYA MENGGUNAKAN METODE CRITICAL CHAIN PROJECT MANAGEMENT (CCPM) - Ahmad Mufahri; Wateno Oetomo (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
There are still many problems in project implementation, such as errors in calculating estimated costs and time needed to complete the project during the planning or management stages that are not appropriate, material problems, labor. , equipment, finances, and unfavorable environment causing delays in project implementation. As a result, cost and time management is needed, to increase the efficiency and effectiveness of project management to get the most out of existing resources. All of that to achieve the objectives of the Level III Brawijaya Hospital Surabaya Building Development project, especially progress in gathering cost (financial), time (timetable) and quality (quality) standards to overcome this problem, the Critical Chain Project Management (CCPM) method can be used as a alternatives in the planning and management of construction projects. This critical chain project management methodology is a method that really avoids multitasking employees because it can cause prolonged work involving activities that are not always the same, which can make employees lose focus on their work. There is also the term buffer. This means the schedule period is added to protect the critical chain for project success. There are two relatively easy approaches to determining buffer size. For the project buffer, the feeding buffer also uses the Cut and Paste Method (C&PM) and the Root Square Error Method (RSEM). Based on the analysis with the application of the critical chain project management method, it was obtained that the feeding buffer was 109 days and the project buffer was 130 days, so that the time obtained to complete the UB Level III Hospital, Suarabaya Building Development project was 164 days. By using the CCPM method, labor cost savings of Rp. 3.099.752.228 00 without Buffer consumption. However, if the buffer is consumed, an additional fee of Rp. 3.099.752.228 00